Dyes and Fleece Types in Prehistoric Textiles from Scandinavia and Germany - Bender, Lise; Walton, Penelope (Journal of Danish Archaeology, 1986)
Dyes and Fleece Types in Prehistoric Textiles from Scandinavia and Germany